Valuing the Teaching Profession Inquiry - Submission from the Teachers’ Work in Schools Research Team - McGrath-Champ, Susan; Wilson, Rachel; Fitzgerald, Scott; Stacey, Meghan; Gavin, Mihajla (Valuing the Teaching Profession Inquiry (Gallop Inquiry), 2020)
The past ten years have seen considerable shifts reported in the amount and nature of work undertaken by teachers in schools. Our programme of research has documented these perceptions, and associated experiences, in detail across two state contexts (NSW and WA). Collectively, our research highlights that public school teachers in this country are experiencing substantial pressure related, for instance, to administrative and data collection requirements, with this difficulty ‘blanketing’ teaching work across such factors as school type, geographical location and level of advantage. At the same time, our research has shown the considerable and context-specific challenges some teachers face in a system that is increasingly stratified, largely due to an ongoing policy of school ‘choice’. Teachers, across our publications, call for greater support from their employer, and wish to feel valued. In this submission to the Valuing the Teaching Profession Inquiry, we summarise our recent relevant publications and provide a list of recommendations for positive policy progress to address current challenges confronting teachers.